Impact of red versus blue light on tolerability and efficacy of PDT: a randomized controlled trial - Gholam, Patrick; Bosselmann, Ina; Enk, Alexander; Müller-Christmann, Christine (Journal der Deutschen Dermatologischen Gesellschaft, 2018)
Various light sources may be used for photodynamic therapy of actinic keratosis since photosensitizing agents are activated by different wavelengths. However, the relative impact of red and blue light irradiation on the efficacy and tolerability of therapy is controversial. Objective The aim of this study is to compare the efficacy and tolerability of therapy with red versus blue light sources, as well as the patients’ evaluation of cosmetic results, clinical response, painfulness and preferred light source for future photodynamic treatments. Methods This is a prospective, single-center, randomized, controlled, open-label study with 28 patients undergoing elective photodynamic therapy. Results Red and blue light sources both showed very good results with a complete response rate of 84 % and 85 % respectively. Pain during photodynamic therapy was 6.1 vs. 5.4 (and 2.1 vs. 1.5 eight hours after therapy) on the visual analogue scale. Although these differences were statistically significant, the clinical relevance is low, since the number of therapy interruptions were equally distributed in both groups, and patients’ subjective evaluation of the treatment showed no personal preference towards the light sources. Conclusion Both light sources showed very good clinical results and satisfactory tolerability in this study.
Gesehen am 05.04.2019